2011
DOI: 10.1074/jbc.m111.227504
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Oligomers of Amyloid-β Peptide Disrupt Membrane Trafficking of α-Amino-3-hydroxy-5-methylisoxazole-4-propionic Acid Receptor Contributing to Early Synapse Dysfunction

Abstract: ␤-Amyloid (A␤), a peptide generated from the amyloid precursor protein, is widely believed to underlie the pathophysiology of Alzheimer disease (AD). Emerging evidences suggest that soluble A␤ oligomers adversely affect synaptic function, leading to cognitive failure associated with AD. The A␤-induced synaptic dysfunction has been attributed to the synaptic removal of ␣-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors (AMPARs). However, the molecular mechanisms underlying the loss of AMPAR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 57 publications
4
91
2
Order By: Relevance
“…The toxicity induced by a-syn oligomers might be a consequence of enhanced Ca 2ϩ influx through NMDA receptors (Kelly and Ferreira, 2006;Martin et al, 2012). Recently, it was shown that soluble A␤ oligomers affect GluR1 phosphorylation and AMPA receptor trafficking through increased calcium influx and activation of calcium-dependent phosphatase calcineurin (Miñano-Molina et al, 2011). Our data fully support a similar mechanism for a-syn oligomers.…”
Section: Discussionsupporting
confidence: 77%
“…The toxicity induced by a-syn oligomers might be a consequence of enhanced Ca 2ϩ influx through NMDA receptors (Kelly and Ferreira, 2006;Martin et al, 2012). Recently, it was shown that soluble A␤ oligomers affect GluR1 phosphorylation and AMPA receptor trafficking through increased calcium influx and activation of calcium-dependent phosphatase calcineurin (Miñano-Molina et al, 2011). Our data fully support a similar mechanism for a-syn oligomers.…”
Section: Discussionsupporting
confidence: 77%
“…It is worth noting that we avoided preparing Ab42o in F12 medium, a frequently employed procedure (De Felice et al, 2007;Lambert et al, 1998;Mairet-Coello et al, 2013;Minano-Molina et al, 2011;Resende et al, 2008;Zhao et al, 2010) given that aged F12 medium by itself, at the same final dilution (1:100), causes neuronal Ca 2þ rises (Zempel et al, 2010). Concerning the characteristics of the Ab42 preparations, the presence of heat-sensitive Ab-derived diffusible ligands was routinely checked by Western blots (Fig.…”
Section: Submicromolar Synthetic Ab42 Do Not Cause Cytosolic Ca 2þ Rimentioning
confidence: 99%
“…It is now widely believed that the accumulation of soluble Aβ is central to the pathogenesis of the disease (Selkoe, 2000). Soluble Aβ oligomers have been shown to induce many of the deficits associated with AD (Shankar et al, 2008;Logan et al, 2011;Miñano-Molina et al, 2011;Reese et al, 2011;Tan et al, 2011;Ferreira et al, 2012). The Aβ oligomers disrupt synaptic function by causing synaptic depression (Kamenetz et al, 2003b;Hsieh et al, 2006b;Santos-Torres et al, 2007;Li et al, 2009;Cerpa et al, 2010;Kessels et al, 2010a;Kessels et al, 2013;Talantova et al, 2013;Tamburri et al, 2013) and blocking long-term potentiation (LTP) (Walsh et al, 2002;Rowan et al, 2005;Shankar et al, 2008;Rammes et al, 2011;Wang et al, 2012;Sivanesan et al, 2013), a cellular model for learning and memory.…”
Section: Introductionmentioning
confidence: 96%